Closing Corn Yield Gaps via Improved Management: A Systems Approach - G. R. Balboa; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2017)
Three corn research trials were conducted during the 2016 growing season. Two studies were conducted at Scandia, KS, (dryland and irrigated) and one at Topeka, KS (dryland). The objective of these trials was to investigate the contribution of different farming systems for closing corn yield gaps. Each experiment consisted of five treatments: common practices (CP), comprehensive fertilization (CF), production intensity (PI), ecological intensification (CF + PI), and advanced plus (AD). Across all three experiments and under dryland and irrigation scenarios, CP presented the lowest yield. In environments with yield response, intensifying production without a balanced nutrition program did not increase yields. A balanced nutrition program substantially increased yields in corn with more relative impact in dryland environments. The absolute yield gap was 86 bu/a for dryland and 75 bu/a for irrigated condition.
Keywords: corn; yield gaps; cropping system